A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze. Issue 9 (2nd May 2016) - Zeng, Biao; Liu, Guang-Da; Zhang, Bao-Bao; Wang, Shan-shan; Ma, Rui; Zhong, Bei-Shan; He, Bai-qiu; Liang, Yan; Wu, Fei-Hua
Abstract: A new triterpene saponin, 3 β, 16 β, 23 α, 28 β, 30 β -pentahydroxyl-olean-11, 13(18)-dien-3 β -yl-[ β -d -glucopyranosyl-(1→2)]-[ β -d -glucopyranosyl-(1→3)]- β -d -fucopyranoside, was named Clinoposaponin D (1 ), together with six known triterpene saponins, buddlejasaponin IVb (2 ), buddlejasaponin IVa (3 ), buddlejasaponin IV (4 ), clinopodisides D (5 ), 11 α, 16 β, 23, 28-Tetrahydroxyolean-12-en-3 β -yl-[ β -d -glucopyranosyl-(1→2)]-[ β -d -glucopyranosyl-(1→3)]- β -d -fucopyranoside (6 ) and prosaikogenin A (7 ), and two known triterpenes, saikogenin A (8 ) and saikogenin F (9 ) were isolated from Clinopodium chinense (Benth.) O. Kuntze. Their structures were elucidated on the basis of 1D, 2D NMR and MS analysis. Meanwhile, the effects of all compounds on rabbit platelet aggregation and thrombin time (TT) were investigated in vitro . Compounds4 and7 had significant promoting effects on platelet aggregation with EC50 value at 53.4 and 12.2 μM, respectively. In addition, the highest concentration (200 μM) of compounds2 and9 shortened TT by 20.6 and 25.1%, respectively. Graphical abstract: